1983
DOI: 10.1007/bf01003969
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative histochemical study of lactate dehydrogenase and succinate dehydrogenase activities in the membrana granulosa of the ovulatory follicle of the rat

Abstract: Using a microdensitometer, lactate dehydrogenase and succinate dehydrogenase activities were measured in the membrana granulosa of the rat ovulatory follicle. Ovaries were removed on each day of the oestrous cycle; oestrus, dioestrus-1, dioestrus-2, and proestrus; and enzyme activities measured in the membrana granulosa as a whole and in four regions within it: peripheral (PR), antral (AR), cumulus oophorus (CO) and corona radiata (CR). Throughout the cycle, lactate dehydrogenase activity was greatest in PR. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Both side-chain cleavage of cholesterol and aromatization of androgens to oestrogens require molecular oxygen (Ryan, 1959;Halkerston et al, 1961). A gradient of biosynthetic activity has been demonstrated by the preferential distribution of key enzymes in the peripheral granulosa layer of rat Graafian follicles (Zoller andWeisz, 1978, 1979;Zoller and Enelow, 1983), which is also optimally placed for the diffusion of hormonal products into neighbouring capillaries. It is, however, recognised that pre-antral follicles are much less competent to perform steroid biosynthesis than are Graafian types (Roy and Greenwald, 1985), and the functional significance of the oxygen gradient in these stages therefore requires further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Both side-chain cleavage of cholesterol and aromatization of androgens to oestrogens require molecular oxygen (Ryan, 1959;Halkerston et al, 1961). A gradient of biosynthetic activity has been demonstrated by the preferential distribution of key enzymes in the peripheral granulosa layer of rat Graafian follicles (Zoller andWeisz, 1978, 1979;Zoller and Enelow, 1983), which is also optimally placed for the diffusion of hormonal products into neighbouring capillaries. It is, however, recognised that pre-antral follicles are much less competent to perform steroid biosynthesis than are Graafian types (Roy and Greenwald, 1985), and the functional significance of the oxygen gradient in these stages therefore requires further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Differences between granulosa and cumulus cells have been reported by other authors. Morphologically, the two cellular types differ (rat and hamster: Zoller and Enelow, 1983;Zoller, 19841, and they do not undergo atresia at the same rate (sheep: Hay et al, 1976). Significant differences in the proteins secreted by ovine granulosa and cumulus cells have been reported (sheep: Moor and Crosby, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, reverse transcriptase subunit was observed only in the cells localized close to the antrum. The presence of a functional differentiation within somatic follicular cells was also suggested by several authors who demonstrated a different expression of many genes, distribution of LH receptors (Amsterdam et al 1975;Bortolussi et al 1977), and location of steroidogenic enzymes (Zoller and Weisz 1978;Zlotkin et al 1986;Tabarowski and Szoltys 1987) and housekeeping enzymes as well (Zoller and Weisz 1979;Zoller and Enelow 1983). It has been proposed, in this context, that cells localized in the basal zone of the mural layer are better differentiated than the antrally situated cells (Amsterdam and Rotmensch 1987).…”
Section: )mentioning
confidence: 94%